Factors involved in the labor market insertion process of the 2014–2015 graduates of the Bachelor of Arts in Modern Languages with Specialization in French and English, Study Plan 2002 of the Foreign Languages Department of the School of Arts and Sciences of the University of El Salvador - De Paz De Paz, Jeymy Guadalupe
The research presented below is the result of an exploratory study carried out with the 2014–2015 graduates of the Bachelor of Arts in Modern Languages with Specialization in French and English of the Foreign Languages Department of the School of Arts and Sciences of the University of El Salvador, with their employers, and with the professors of this Department. The research was developed following a qualitative–quantitative methodology with the purpose of studying the factors involved in the labor market insertion process faced by these graduates. Among the most noticeable findings in the data triangulation chapter, two factors are highlighted which are: the trilingual ability that these graduates have, and the lack of preparation in their minor field. Based on the above, as a general suggestion, a call is made to the authorities of this Department to analyze, evaluate, and execute a prompt update to the study plan 2002 of this career with the purpose to include more practical spaces in which the student may apply the theory studied; thus, to gain the essential experience that would facilitate them the finding of a job place in their minor.